Digital Fundraising Zakat: A Study on the Impact of Social Media Marketing and Crowdfunding - Rohman, Hilma Fanniar; Amrullah, Amrullah; Ridha, Muhammad (JURNAL EKONOMI SYARIAH, 2024)
Introduction to The Problem: Zakat is an obligation for a Muslim or a body that has met the requirements (Nisab and haul). Islam obliges to pay it to amil zakat institutions. The potential of a large Muslim population in Indonesia is directly proportional to the existing potential. However, the national zakat revenue is not proportional to the existing potential. the development of technology is accelerating and we are entering the digital era. causing Digital Fundraising Zakat to have an important role in the developments that occur in the dynamics of Zakat Fund Raising. Social Media Marketing and Crowdfunding Platform have an important role in Digital Fundraising Zakat.Purpose/Objective Study: This study aims to analyze Social Media Marketing and crowdfunding Platforms on the Decision to pay zakat in Ciamis Regency.Design/Methodology/Approach: The population of this research is all Muzakki in Ciamis Regency, while the sample is all Muzakki managers in Ciamis Regency who are under the auspices of Lembaga Amil Zakat Infaq Shadaqah Muhammadiyah Ciamis. Data was collected through questionnaire instruments and analyzed using descriptive statistical analysis techniques and Structural Equation Model (SEM) analysis.Findings: Based on the results of data analysis, social media marketing, and crowdfunding platforms are proven to have a significant and positive influence on people's decision to give zakat. This research has shown that the strategy of zakat institutions that utilize digital technology influences optimizing zakat collection.Paper Type: Research Article